Improving artemisinin and essential oil production from Artemisia plant through in vivo elicitation with gamma irradiation nano-selenium and chitosan coupled with bio-organic fertilizers - Sayed, Tarek E.; Ahmed, El-Sayed S. (Frontiers in Energy Research, 2022)
Artemisia plants process potential bioactive secondary metabolites such as artemisinin and essential oil. They are useful in controlling potential pests and microbes and have a therapeutic effect. The commercial production of artemisinin and essential oil is limited to regarding the worldwide demand. Urgent attempts must be undertaken to improve the production of bioactive secondary metabolites. The objectives of this experiment were to increase the production and improve the quality of bioactive secondary metabolites in order to limit the use of agrochemicals. Therefore, a field experiment was conducted during the 2018 and 2019 seasons. Treatments included three elicitations (gamma irradiation, nano-selenium, and chitosan) and three kinds of fertilizers (NPK, Moringa leaf extract, and humic acid). The experiment was conducted as a factorial with a completely randomized block. The designs and treatments were arranged in a split–split plot with three replicates. A single application of elicitors showed that chitosan > nano-selenium, chitosan > gamma irradiation, and Moringa > humic acid > NPK in plants’ artemisinin and essential oil content, while the interaction showed a significant synergistic relationship between elicitors and the fertilizers in enhancing the quantity and quality of artemisinin and essential oil of Artemisia plants. Without using any pesticides, there was no infection that appeared in Artemisia plants, this could be due to the enhancement of bioactive secondary metabolite production.